Bottom‐Up Quasi‐Epitaxial Growth of Hybrid Perovskite from Solution Process—Achieving High‐Efficiency Solar Cells via Template​‐Guided Crystallization - Zhang, Hengkai; Qin, Minchao; Chen, Zhiliang; Yu, Wei; Ren, Zhiwei; Liu, Kuan; Huang, Jiaming; Zhang, Yaokang; Liang, Qiong; Chandran, Hrisheekesh Thachoth; Fong, Patrick W. K.; Zheng, Zijian; et al. (Advanced materials (Weinheim), 2021)
Epitaxial growth gives the highest‐quality crystalline semiconductor thin films for optoelectronic devices. Here, a universal solution‐processed bottom‐up quasi‐epitaxial growth of highly oriented α‐formamidinium lead triiodide (α‐FAPbI3) perovskite film via a two‐step method is reported, in which the crystal orientation of α‐FAPbI3 film is precisely controlled through the synergetic effect of methylammonium chloride and the large‐organic cation butylammonium bromide. In situ GIWAXS visualizes the BA‐related intermediate phase formation at the bottom of film, which serves as a guiding template for the bottom‐up quasi‐epitaxial growth in the subsequent annealing process. The template‐guided epitaxially grown BAFAMA perovskite film exhibits increased crystallinity, preferred crystallographic orientation, and reduced defects. Moreover, the BAFAMA perovskite solar cells demonstrate decent stability, maintaining 95% of their initial power conversion efficiency after 2600 h ambient storage, and 4‐time operation condition lifetime enhancement. A universal solution‐processed bottom‐up quasi‐epitaxial growth of highly oriented α‐FAPbI3 perovskite film is achieved through the synergetic effect of methylammonium chloride and a large‐organic cation. In situ GIWAXS visualizes the BA‐related intermediate phase formation at the bottom, which serves as a guiding template for the bottom‐up quasi‐epitaxial growth in the subsequent annealing process.